Estudio de prefactibildad para la implementación de una planta productora de cerveza artesanal con camu camu endulzada con stevia - De La Torre Parodi, Mariana (2018)
The following preliminary study has as main objective, obtain the title of Industrial Engineer through the determination of the technological, economic and financial viability for the installation of a camu camu craft beer brewing plant sweetened with stevia. It is also desired to identify potential consumers, in order to be able to estimate the demand and evaluate the influential forces in the market. This project idea came because of the growing demand for craft beer and stevia. In the same way we want to innovate and make a change of taste in beer, offering an "easy to pass" product, as it contains a sweet and fruity touch based on an innovative fruit camu camu. In the first chapter, are the generalities of the product, its definition and main characteristics. Based on this, the substitutes and complementary products are analyzed, in order to have a clear idea of the market context. In the second chapter the market study is carried out, where the research guidelines have been established and the analysis of market demand and supply is carried out. With this information, you can get an estimate of the demand for the project. The availability of raw materials is also investigated. The third chapter presents an analysis of possible locations for the project, including the evaluation of important factors for selecting both macro and micro location. The fourth chapter presents an analysis of the market, the productive resources, the technology and the point of balance, to determine the annual size of our production plant. The fifth chapter consists mainly of project engineering, technical definition of the product and its design, as well as its diagram production process and material balance to determine plant capacity. The sixth chapter consists of the layout of our plant and how it will be constituted, a plan of plant will be realized and everything related to logistics will be analyzed. In the seventh chapter, the economic and financial aspects of the project will be determined and analyzed so that the eighth chapter concludes whether the project is financially and economically viable. Finally, in the last chapter, areas that will suffer some kind of impact for the project and social indicators will be analyzed.